2019
DOI: 10.2134/agronj2019.01.0056
|View full text |Cite
|
Sign up to set email alerts
|

A Growth Model to Estimate Shoot Weights and Leaf Numbers in Tea

Abstract: Increases in plant weight are strongly correlated with the amount of solar radiation that the plants receive. However, tea (Camellia sinensis) growth models are limited in their ability to integrate solar radiation into the predictions. In this study, we developed a predictive model for estimating tea shoot weights based on solar radiation and air temperatures. We combined information on daily solar radiation and daily air temperature to estimate the dry weight and fresh weight of a shoot in a tea crop. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…High maize yields tend to be obtained under conditions of relatively low temperature and high solar radiation [15]. Theoretically, crop yields can therefore be improved by enhancing radiation-use efficiency (RUE) [16,17], a parameter used to quantify the relationship between solar radiation and biomass production, which is the input basis for growth and yield models [18,19]. Several studies with regards to climate change and RUE have been reported recently [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…High maize yields tend to be obtained under conditions of relatively low temperature and high solar radiation [15]. Theoretically, crop yields can therefore be improved by enhancing radiation-use efficiency (RUE) [16,17], a parameter used to quantify the relationship between solar radiation and biomass production, which is the input basis for growth and yield models [18,19]. Several studies with regards to climate change and RUE have been reported recently [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cultivars used in the early period of the experiments are no longer cultivated today. It is also difficult to thoroughly account for other factors that may affect crop growth, such as soil fertility, insects, disease, and plant density ( Altieri & Nicholls, 2003 ; Chen, Yamagishi & Kishino, 2014 ; Chen et al, 2019 ; Chen, 2019 ; Li, Dai & Chen, 2022a , 2022b ); as well as for human-induced effects, such as improving technology, modern management, and differences in practices of cultivators ( Chen, 2018 , 2019 ), especially for over nine decades of observations. Nowadays, climate change also includes the increasing frequency of extreme climatic events, which results in frequent agricultural meteorological disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the coefficient for temperature-driven effect ( TF ) can be expressed as: where T 0 denotes the optimal temperature on tea growth. Following the work by Chen et al [ 23 ], T 0 was set to be 23 °C, and β was estimated to be 20 °C. The temperature-dependent tea growth rate can then be expressed as: …”
Section: Methodsmentioning
confidence: 99%
“…Temperature is a determinant factor and has significant impact on processes related to ecological community, particularly predator–prey or consumer–resource interactions [ 20 , 21 ]. For example, the growth rate of crops, the oviposition, and the lifespan of pests can be altered by temperature [ 22 , 23 ]. For predator–prey systems, variations in temperature usually have a nonlinear effect on the short-term interaction strength by regulating the foraging and attack rates of predators [ 24 ].…”
Section: Introductionmentioning
confidence: 99%